(untitled) (Canadian Dermatology Today, 2022)
Systemic isotretinoin is a commonly employed treatment for acne. Currently, the Health Canada approved product monograph contains a warning that aggressive chemical dermabrasion and cutaneous laser treatment be avoided in patients for a period of 5-6 months after the end of treatment because of the risk of hypertrophic scarring in atypical areas, and more rarely hyper- or hypo-pigmentation in treated areas. This recommendation, derived largely from case reports or studies conducted in the 1980s, is based on the belief that systemic isotretinoin therapy contributes to abnormal wound healing and increased risks for scarring. However, there is a growing body of evidence that sheds new light on these claims, and several groups have recently released consensus recommendations addressing these concerns. This paper aims to summarize our current understanding and the most recent evidence-based clinical recommendations regarding the safety of procedural interventions in the setting of systemic isotretinoin therapy.